Struktur dan Interpretasi Makna Simbolik dalam Cerita Rakyat Kunaung oleh Iskandar Zakaria - Reska Wati; Maizar Karim; Liza Septa Wilyanti (Prodi Sastra Indonesia, FKIP Universitas Jambi, 2023)
Abstract This study aims to describe the structure and interpretation of Symbolic meaning. The structure is a story building element including: elements of theme, plot, setting, characters, and characterizations, as well as the mandate. Interpreting the symbolic meaning in the story is expected to increase knowledge. This research uses descriptive qualitative research method. The data are in the form of words, sentences, and paragraphs in the story of Belalai Raja, Beranak Beruk story, and the story of Nek Demang Nunggit in Kunaung by Iskandar Zakaria 1981. The data collection technique used in this research is literature study technique. The data analysis technique is done by classifying the data related to the structure and interpreting the symbolic meaning. Then describe the structure and symbolic meaning and finally draw conclusions from the data that has been describe. The results obtained in this study are the structure of the theme, plot, setting, characters and characterizations, as well as mandate. The three stories contain different themes. The story of the king’s trunk contains the theme of injustice, the story of giving birth to a monkey bears the theme of patience and gratitude and the story of Nek Demang Nunggit contains the theme of a gamble ending in disaster. All three stories use a forward plot. The setting used includes the setting of place, time, and atmosphere. Characters in the story are grouped into main characters, protagonists, antagonists, developing, and additional. The story of the king’s trunk contains a mandate that is to be a fair and wise leader, the story of the berak bears contains a mandate that is to accept the test patiently and not give up. The story of Nek Demang Nunggit contains a mandate that is not to bet anything in a prohibited game such as fighting cocks. The symbols contained in the story of the king’s trunk are the elephant symbol which means wisdom, the story of Beranak Beruk has a ring symbol which means magical power and the Nek Demang Nunggit story has a rooster symbol which means strength. The three stories can be concluded to have a complete structure. The three stories contain interpretations of life views and character values that provide good values. Abstrak Penelitian ini bertujuan mendeskripsikan struktur dan interpretasi makna simbolik. Penelitian ini menggunakan metode penelitian deskriptif kualitatif. Teknik pengumpulan data yang digunakan dalam penelitian ini yaitu teknik studi pustaka. Teknik analisis data dilakukan dengan mengklasifikasikan data terkait struktur dan menginterpretasikan makna simbolik. Kemudian mendeskripsikan struktur dan makna simbolik dan yang terakhir menarik kesimpulan dari data-data yang telah dideskripsikan. Hasil penelitian yaitu ketiga cerita mengandung tema yang berbeda. Cerita Belalai Raja mengandung tema ketidakadilan, cerita Beranak Beruk mengandung tema kesabaran dan rasa syukur dan cerita Nek Demang Nunggit mengandung tema pertaruhan berakhir malapetaka. Ketiga cerita menggunakan alur maju. Latar yang digunakan meliputi latar tempat, waktu, dan suasana. Tokoh dalam ketiga cerita dikelompokan atas tokoh utama, protagonis, antagonis, berkembang, dan tambahan. Cerita Belalai Raja mengandung amanat yaitu jadilah seorang pemimpin yang adil dan bijaksana. Cerita Beranak Beruk mengandung amanat yaitu menerima ujian dengan sabar dan tidak berputus asa. Cerita Nek Demang Nunggit mengandung amanat yaitu jangan mempertaruhkan sesuatu dalam permainan yang dilarang seperti mengadu ayam. Adapun simbol yang terdapat dalam cerita Belalai Raja yaitu simbol gajah yang bermakna kebijaksanaan, cerita Beranak Beruk terdapat simbol cincin yang bermakna kekuatan magis dan cerita Nek Demang Nunggit terdapat simbol ayam jago yang bermakna kekuatan. Mengandung interpretasi pandangan hidup dan nilai karakter yang memberikan nilai kebaikan.